Postawy wrażliwości społecznej versus postawy pragmatyczne i ich osobowościowe uwarunkowania - Czerniawska, Mirosława (Wydawnictwo Naukowe UAM, 2016)
The main aim of this research is investigation of social sensitivity attitudes and pragmatic attitudes. It was assumed that these attitudes depend on personality traits, like empathy and Machiavellian guilt. The study group consisted of 325 students. The Empathic Understanding of Others Questionnaire (Węgliński) and Mach V Scale (Christie and Geis) were used. The attitudes were diagnosed on the basis of the set of views (two pairs of statements from the publication edited by Reykowski). The study results show that social sensitivity attitudes were accepted by students having high empathy indices. Students having high Machiavellianism show a pragmatic attitude toward life.
Social Sensitivity Attitudes versus Pragmatic Attitudes and their Personality Conditions
Keywords: attitudes; social sensitivity; pragmatism; personality traits; empathy; Machiavellianism